Clinical, Biochemical and Hormonal Profile of Polycystic Ovary Syndrome (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: The polycystic ovary syndrome is a heterogenous condition, the pathophysiology of which is multifactorial. It is considered as a systemic and metabolic disorder like hyperglycemia and insulin resistance with increased risk of type II diabetes mellitus and cardiovascular diseases.Objective: The purpose of the present study was to analyze the clinical, biochemical and hormonal profile of patients PCOS and to find out correlations among them.Methodology: This cross-sectional observational study was done including 100 diagnosed cases of PCOS attending the GOPD, BSMMU Hospital. This study was done to analyze the clinical, biochemical and hormonal characteristics of PCOS patients and to observe the correlations among them.Result: The mean age of study populations was 22.7± 6.9 years and more than half of them were overweight or obese. Menstrual abnormality like oligomenorrhoea and secondary amenorrhoea was found in 95% cases and 5% were eumenorrhic. Prevalence of hirsutism and subfertility was 69% and 50% respectively. More than half (52%) of cases had LH/FSH ratio >2 which is taken to be significant. About one-third (30%) of cases had total testosterone level above the reference range with a mean value of serum testosterone 71.4±27.9 ng/dL.Conclusion: Significant positive correlation was found among increased BMI, increased LH/FSH ratio, serum testosterone and serum TSH level. Further studies are needed to corroborate our findings and to find out the clinical, biochemical and endocrinological characteristics of our women of PCOS.Journal of National Institute of Neurosciences Bangladesh, 2017;3(2): 94-98